2012
DOI: 10.1128/ec.05102-11
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptome Changes Underlying Colony Growth in the Opportunistic Human Pathogen Aspergillus fumigatus

Abstract: Aspergillus fumigatus is the most common and deadly pulmonary fungal infection worldwide. In the lung, the fungus usually forms a dense colony of filaments embedded in a polymeric extracellular matrix. To identify candidate genes involved in this biofilm (BF) growth, we used RNA-Seq to compare the transcriptomes of BF and liquid plankton (PL) growth. Sequencing and mapping of tens of millions sequence reads against the A. fumigatus transcriptome identified 3,728 differentially regulated genes in the two condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
117
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(130 citation statements)
references
References 76 publications
6
117
0
7
Order By: Relevance
“…Moreover, biochemical inhibition of chitinase activity significantly affected eDNA release. It was also reported in an A. fumigatus biofilm study using microarray analysis that class IV chitinase mRNA was upregulated ϳ5-fold in 48-h biofilms (53), whereas Gibbons and colleagues did not identify this expression, but they explained this difference by the potential production of pseurotin A, a potent inhibitor of chitinases (54). Given that chitinases are markers of autolysis, this process is a possible mechanism for eDNA release.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, biochemical inhibition of chitinase activity significantly affected eDNA release. It was also reported in an A. fumigatus biofilm study using microarray analysis that class IV chitinase mRNA was upregulated ϳ5-fold in 48-h biofilms (53), whereas Gibbons and colleagues did not identify this expression, but they explained this difference by the potential production of pseurotin A, a potent inhibitor of chitinases (54). Given that chitinases are markers of autolysis, this process is a possible mechanism for eDNA release.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for these repeated failures remain unknown, but they could be due to the large size of the genes (Ͼ8 kb), their in vivo three-dimensional conformation, or the presence of one of these AGS genes (AGS1) in the subtelomeric region of a chromosome (chromosome 3), which is always difficult to manipulate genetically (11). Nevertheless, the lack of a growth phenotype in a triple AGS mutant totally devoid of ␣1,3 glucans showed definitively that the ␣1,3 glucans that are the major cell wall component are fully dispensable for A. fumigatus vegetative growth.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the transcriptional control of each metabolic cluster and thus the concentration of the secondary metabolite linked to their activity depends on mechanisms exerted on various cluster functions, such as oxidoreduction, transcriptional regulation, or transport (13,74,76). Thus, we decided to study the genomic flanking regions of specific PKS-or NRPS-coding genes shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, this powerful technique arises as an efficient tool for transcriptomic analyses in the genus Aspergillus, as shown in 2010 by Wang and coworkers (11), who published the first RNA-seq-based transcriptomic study of this genus. In these last 2 years, the RNA-seq-based studies involving Aspergillus species analyzed the temperature effect on secondary metabolite synthesis, biofilm formation, the response to lignocellulose, or domestication in A. fumigatus, A. flavus, A. niger, or A. oryzae, respectively (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%